2015
DOI: 10.1038/ng.3414
|View full text |Cite
|
Sign up to set email alerts
|

Intron retention is a widespread mechanism of tumor-suppressor inactivation

Abstract: A substantial fraction of disease-causing mutations are pathogenic through aberrant splicing. Although genome profiling studies have identified somatic single-nucleotide variants (SNVs) in cancer, the extent to which these variants trigger abnormal splicing has not been systematically examined. Here we analyzed RNA sequencing and exome data from 1,812 patients with cancer and identified ∼900 somatic exonic SNVs that disrupt splicing. At least 163 SNVs, including 31 synonymous ones, were shown to cause intron r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
290
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(333 citation statements)
references
References 67 publications
(45 reference statements)
20
290
0
4
Order By: Relevance
“…It has been suggested that IR is deliberately used as a regulatory step to decrease the expression of target genes (BRAUNSCHWEIG et al 2014;JUNG et al 2015).Our data showed that the majority of sex-biased IR events located in CDS introduced PTCs (> 80%, Figure 2D). We therefore asked whether sex-biased IR events with PTC are associated with gene expression changes.…”
Section: Introns That Are Differentially Retained In Ovary and Testismentioning
confidence: 58%
See 2 more Smart Citations
“…It has been suggested that IR is deliberately used as a regulatory step to decrease the expression of target genes (BRAUNSCHWEIG et al 2014;JUNG et al 2015).Our data showed that the majority of sex-biased IR events located in CDS introduced PTCs (> 80%, Figure 2D). We therefore asked whether sex-biased IR events with PTC are associated with gene expression changes.…”
Section: Introns That Are Differentially Retained In Ovary and Testismentioning
confidence: 58%
“…Recent studies have identified numerous differentially regulated AS events in a variety of conditions (MCINTYRE et al 2006;WANG et al 2008;TELONIS-SCOTT et al 2009;GAN et al 2010;CHANG et al 2011;HARTMANN et al 2011;STURGILL et al 2013;WANG et al 2014) and highlighted the role of IR as a cellular mechanism to influence mRNA abundance and alter biological outcomes (BRAUNSCHWEIG et al 2014;JUNG et al 2015;EDWARDS et al 2016;MAUGER et al 2016;NI et al 2016;MIDDLETON et al 2017;NARO et al 2017). However, the occurrence and extent of sex-biased IR has not been addressed and the role of sex chromosomes in the modulation of splicing has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work, however, has shown that intron retention might be a conserved and more common mode of transcript regulation than previously appreciated (Galante et al 2004;Braunschweig et al 2014;Boutz et al 2015;Mudvari et al 2015;Wong et al 2016), with examples found in hematopoiesis (Wong et al 2013;Edwards et al 2016), T-cell activation (Ni et al 2016), and neuronal development and activity (Bell et al 2010;Yang et al 2012;Yap et al 2012). Inappropriate intron retention has also been identified in diverse genetic diseases, including cancer (Seifert et al 2006;Tanackovic et al 2011;Dvinge and Bradley 2015;Jung et al 2015;Ortega-Recalde et al 2015;Kallabi et al 2016). Although there are tools that can predict the effects of sequence variants on alternative exon use or alternative 5 ′ donor or 3 ′ acceptor splice sites (Jian et al 2014), to our knowledge, there are no computational tools to predict intron retention from sequence data.…”
Section: Intron Retention As a Mechanism Of Genetic Diseasementioning
confidence: 99%
“…Intron retention regulation has been observed in different cell types (Braunschweig et al 2014), during specific differentiation processes such as erythropoiesis (Pimentel et al 2016) or granulocyte differentiation (Wong et al 2013). Intron retention also plays a role in cancer as a mechanism of tumor suppressor inactivation (Jung et al 2015). Since Acinus controls the splicing of a subset of introns, it could represent a good candidate for the specific control of IR in a precise biological context, as was observed for hnRNPLL in intron retention regulation in T cells (Cho et al 2014).…”
Section: A Role For Acinus In Splicing Regulationmentioning
confidence: 99%